Computational analysis of the effect of hydrogen peroxide addition on premixed laminar hydrogen/air flames. (15th October 2021) - Tingas, Efstathios-Al.
Highlights: The H2 O2 addition to laminar premixed H2 /air flames leads to: A great increase of the laminar flame speed, the heat release rate and NOx. A reaction zone broadening due to the increased radical pool. Change in the flame structure due to either H2 O2 +H = H2 O + OH or H2 O2 (+M) = 2OH(+M). The enhancement of the flame's stability. Abstract: In the current work, the effect of H2 O2 addition on the flame structure, laminar flame speed and NOx emissions is investigated in the context of 1D laminar premixed H2 /air flames at Tu = 300 and 600 K, p = 1 and 30 atm, ϕ = 0.5. Mathematical tools from the computational singular perturbation approach are used in order to identify the key chemical and transport mechanisms. The H2 O2 addition causes a significant increase to the laminar flame speed (sL ), heat release (Q) and NOx emissions. Indicatively, 10% H2 O2 addition (per fuel volume) at Tu = 300 K, p = 1 atm results in 72% increase of sL, 100% increase of Q, and 140% increase of the mass fraction of NO. Depending the conditions the flame structure is altered through the chain carrying reaction 10f (H2 O2 + H → H2 O + OH) or the chain branching 9f (H2 O2 (+M) → 2OH (+M)); the first is favored at low temperatures/pressures while the latter is favored at sufficiently high temperatures/pressures. Both reactions boost the radical pool generation, therefore contributing to the broadening of the reaction zone. The reaction with the largest contribution to Q that is mostly affected (decreased) by the addition of H2 O2 is reaction 21 (H + O2 (+M) ↔ HO2 (+M)). Moreover, the H2 O2 addition enhances the stability of the flame. Finally, the increased production of NO is mainly associated with the increased temperature that is reached with the addition of H2 O2 .